(untitled) (Pedagogy of Higher and Secondary Education, 2008)
The article deals with the problem of peculiarities of putting into practice interactive methods of learning at the lessons of reading in primary school. The active model of learning provides the use of the methods stimulating cognitive and self-directed activities of a primary school pupil at the lessons of reading. Interactive learning comprises modelling life situation, using role plays, general problem solving though the analysis of conditions and an appropriate situation.